"Studies of the Uptake of Nitrate in Barley. I. Kinetics of 13NO3− Influx" by M.Y. Siddiqi, A.D.M. Glass, T.J. Ruth, and T.W. Rufty, Jr., Plant Physiology (1990) 93:1426–1432. Issue 1 (16th November 2020) - Sinclair, Thomas R.
Abstract: This article is part of a series of brief commentaries to highlight papers that have resulted in important and distinctly new perspectives in crop science. A criterion for selection of papers is that they must have been published at least 20 yr ago to allow for a long‐range perspective in assessment of the papers. The current article briefly reviews the paper by M.Y. Siddiqi, A.D.M. Glass, T.J. Ruth, and T.W. Rufty, Jr. published in 1990 that investigated the kinetics of nitrate influx by barley ( Hordeum vulgare L.) seedlings. Using 13 NO3 −, they documented the existence of two influx systems. One was inducible and nitrate influx saturated under low nitrate concentrations. The second was noninducible and expressed a linear increase in nitrate influx over high nitrate concentrations. Key transformative results from this study were the demonstration that both systems were under negative feedback control based on root nitrate concentration.